2013
DOI: 10.1007/s00540-013-1688-3
|View full text |Cite
|
Sign up to set email alerts
|

A temporary decrease in twitch response following reversal of rocuronium-induced neuromuscular block with a small dose of sugammadex in a pediatric patient

Abstract: We report a temporary decrease in twitch response following reversal of rocuronium-induced neuromuscular block with a small dose of sugammadex in our dose-finding study in pediatric patients. A 19-month-old female infant (9.6 kg, 80 cm) was scheduled for elective cheiloplasty surgery. Anesthesia was induced with nitrous oxide 50 % and sevoflurane 5 % and maintained with air, oxygen, sevoflurane 3 %, and fentanyl (total, 3 μg/kg). Neuromuscular monitoring was performed at the adductor pollicis muscle after indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Two of 10 patients who received 1 mg/kg of sugammadex at a depth of block of 1–2 PTCs met this definition in a Phase 2 trial [ 8 , 10 ]. Three patients in the same trial and one pediatric patient in a case report [ 11 ] did not completely meet the criteria for recurrent block, however, a temporary decrease in twitch response following sugammadex reversal was observed. In these reports, all patients had received less than the 4 mg/kg recommended dose of sugammadex (0.5 or 1 mg/kg) at a depth of block of 1–2 PTCs [ 8 , 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of 10 patients who received 1 mg/kg of sugammadex at a depth of block of 1–2 PTCs met this definition in a Phase 2 trial [ 8 , 10 ]. Three patients in the same trial and one pediatric patient in a case report [ 11 ] did not completely meet the criteria for recurrent block, however, a temporary decrease in twitch response following sugammadex reversal was observed. In these reports, all patients had received less than the 4 mg/kg recommended dose of sugammadex (0.5 or 1 mg/kg) at a depth of block of 1–2 PTCs [ 8 , 10 , 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…Three patients in the same trial and one pediatric patient in a case report [ 11 ] did not completely meet the criteria for recurrent block, however, a temporary decrease in twitch response following sugammadex reversal was observed. In these reports, all patients had received less than the 4 mg/kg recommended dose of sugammadex (0.5 or 1 mg/kg) at a depth of block of 1–2 PTCs [ 8 , 10 , 11 ]. The mean time from sugammadex administration to recovery of TOFR >0.9 (prior to recurrence) was 6.9 (range 3.6–11.5) minutes [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Albeit rare, anecdotal reports have demonstrated the potential for this phenomenon even with sugammadex. [94][95][96][97] One final issue that should be addressed with sugammadex is the concern that it may interfere with hormonal contraceptive agents. In vitro binding studies have demonstrated the binding of progesterone thereby decreasing the free plasma concentration.…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…When neostigmine is used to reverse deep NMB, a mean of 50.4 min is necessary to reach a TOF ratio of 0.9 [9]. Doses of sugammadex below 1 mg.kg-1 have been shown to be initially effective to reverse rocuronium-induced deep NMB, but lead to the gradual reappearance of the NMB in both adults [15] and children [16]. In contrast, sugammadex doses ranging from 1 to 2 mg.kg-1 have shown to reverse rocuronium-induced deep NMB with significant time variability (TOF ratio ≥ 0.9 is obtained from 1.8 to 15.2 min) [17].…”
Section: Deep Neuromuscular Blockade (Post-tetanic Count=1-2)mentioning
confidence: 99%